2020
DOI: 10.3920/wmj2019.2532
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium graminearum populations from maize and wheat in Ontario, Canada

Abstract: Ontario has suffered widespread epidemics of Fusarium Head Blight or Gibberella Ear Rot roughly every five years since the late 1970s. We undertook a study of the chemotype and genotype of Fusarium graminearum isolated from 1,800 samples of wheat and maize collected across the cereal growing areas over three years. 468 isolates obtained were genotyped and 60 were selected for chemotyping. The dominant genotype has remained the native 15-acetyldeoxynivalenol (15-ADON) population. Approximately 20% of the strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…2,7 F. graminearum has two main chemotypes: the 3-or 15-acetyl DON producers (3ADON and 15ADON) (Figure 1). 8,9 This arises from altered activity of their respective TRI8 enzymes that deacetylate the 3,15-diacetyl DON precursor to 3ADON and 15ADON, respectively. 8 The two enzymes have different physical and biochemical properties.…”
Section: Plantsmentioning
confidence: 99%
“…2,7 F. graminearum has two main chemotypes: the 3-or 15-acetyl DON producers (3ADON and 15ADON) (Figure 1). 8,9 This arises from altered activity of their respective TRI8 enzymes that deacetylate the 3,15-diacetyl DON precursor to 3ADON and 15ADON, respectively. 8 The two enzymes have different physical and biochemical properties.…”
Section: Plantsmentioning
confidence: 99%
“…As mentioned above, this trend has also been observed in wheat at these locations. Crippin et al (2020) suggested that the dominance of 15ADON populations in wheat farms in Ontario is due to the stability of maize farms, coupled with the practice of minimum tillage, which increases the biomass proportion of overwintered ascocarps. These ascocarps can act as a primary inoculum in newly established wheat fields and can result in the establishment of further 15ADON populations.…”
Section: Trichothecene Mycotoxin Chemotypes and The Population Genetic Structures Of Fusarium Species Causing Fhb In Wheat And Barleymentioning
confidence: 99%
“…Despite concerted efforts by plant breeders to develop Fusarium resistance crops, high prevalence of Fusarium damage and DON contamination in cereals is still a major problem in Canada and in other temperate parts of the world ( Sabater-Vilar et al, 2007 ; Mwaniki, 2017 ; Crippin et al, 2020 ). Indeed, analyses of feedstuffs and complete feed samples collected from 100 countries from 2008 to 2017 indicated prevalence of DON was 64% in samples from North America ( Gruber-Dorninger et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%